Rasio Keuangan dan Mekanisme Corporate Governance terhadap Financial Distress di masa pandemi Covid-19 - Lidia Nurhayati; Lely Dahlia (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to determine the effect of financial ratios and corporate governance mechanisms on financial distress during the COVID-19 pandemic. The samples obtained were 20 transportation companies in the 1st quarter of 2020, the 2nd quarter of 2020, and the 3rd quarter of 2020 in order to obtain 60 observational data. This study uses the method of partial regression analysis (Partial Least Square/PLS). The results of this study indicate that leverage has a significant positive effect on financial distress, profitability has a significant negative effect on financial distress, and managerial ownership has a significant negative effect on financial distress. The limitation of this study is that this study only uses three independent variables, while there are still many variables used to influence financial distress. The contribution of this research is to be able to provide an overview of the company's financial condition, provide recommendations for appropriate models to measure the company's financial distress and assist in making investment decisions.